DAMPAK SOSIAL KEKERASAN TERHADAP JEMAAT AHMADIYAH DI LOMBOK DAN UPAYA RESOLUSI KONFLIK - Amrullah, Moh. Asyiq; Mustain, Mustain; Wardatun, Atun (LP2M IAIN Mataram, 2010)
This study examines two issues; first, the social aftermaths of the violence and, second, the conflict resolution sponsored by the government of West Nusa Tenggara Province. The study maintains that the violence against Ahmadiyah members has stimulated internal solidarity because, among other things, the community believes that the violence is a challenge to defend their faith. Such a strengthening communal bond has made them survive despite the fact that they lose their political rights as citizens. Although they are now living temporarily for years in a boarding house provided by the local government, some community members have begun their life and worked normally. On the other hand, there has been seemingly no serious effort ever made by the government to resolve the conflict in terms of conflict anticipation, reconstruction of destroyed buildings, peace-building and reconciliation. The governmentâs effort that is aimed to anticipate conflicts is realized through the issuance of joint decree between three ministerial offices. The reason for the issuance of the joint decree is because this is seen as an effective way to anticipate conflicts since the government and the opponents of Ahmadiyah conceive of the conflict as a religious or faith-based conflict in which reconciliation might be futile.